The Fair Rubber Association: where fairly traded rubber hits the road. (1st June 2021) - Kunz, Martin
Abstract : This article reflects on the evolution of rubber (natural latex) production and aspects of its bloody, colonial history, noting the varied applications of rubber in objects around us. The author shows why rubber is a product in need of a Fair Trade label to promote good conditions for rubber tappers, farmers and workers, despite being rejected as a product candidate by FLO international. Lessons are drawn from the evolution of Fairtrade certification criteria and design flaws and the barriers this represents for other major commodities like rubber to be added. Building on the innovations in criteria, representation and premium system developed for Fair Trade Tea plantations, the Fair Rubber Association's approach is described, including the dynamics of the market for workers and small-scale producers. This essay explores issues of measuring labour costs, determining fair prices for workers and farmers. The article shows how this was resolved for Fair Trade rubber and the challenges to be overcome of extreme price sensitivity of major users (like the car industry) and rise of synthetic rubber.